Recurrence of autoimmune hepatitis cholestatic variant syndromes after liver transplantation affects graft and patient survival - Ronca, Vincenzo; Parente, Alessandro; Lytvyak, Ellina; Hansen, Bettina E.; Hirschfield, Gideon; Bonder, Alan; Ebadi, Maryam; Elwir, Saleh; Alsaed, Mohamad; Milkiewicz, Piotr; Janik, Maciej K.; Marschall, Hanns Ulrich; et al. (JHEP Reports, 2025)
Background & Aims: A significant proportion of patients with variant syndromes (VSs), namely autoimmune hepatitis/primary biliary cholangitis or autoimmune hepatitis/primary sclerosing cholangitis, require liver transplantation (LT) despite treatment. The frequency of disease recurrence and the effect on graft survival are yet to be clarified. The aim of this international, multicentric, retrospective study is to evaluate the risk factors associated with recurrence and the impact of the disease recurrence after LT on graft and patient survival. Methods: We evaluated 166 patients undergoing LT for VS in 33 centers in North America, South America, Europe, and Asia. Clinical data before and after LT, biochemical data within the first 12 months after LT, and immunosuppression after LT were analyzed to identify patients with a higher risk of recurrence of autoimmune disease based on a histological and radiological diagnosis. Cumulative probabilities of graft and overall survival after LT were calculated using a semi-Markov model. Results: The autoimmune pattern of recurrence resembled the original VS in 19 cases (61%). Recurrence of autoimmune liver disease (rALD) after LT was observed in 23% and 33% of patients after 5 and 10 years, respectively. Increased alkaline phosphatase (hazard ratio [HR] 1.60, 95% confidence interval [CI] 1.13–2.25, p <0.01) and alanine aminotransferase (HR 1.25, 95% CI 1.01–1.53, p = 0.03) at 12 months after LT and acute rejection (HR 3.58, 95% CI 1.60–7.73, p <0.01) were associated with a higher risk of VS recurrence, whereas the use of predniso(lo)ne was associated with a reduced risk (HR 0.30, 95% CI 0.14–0.64, p <0.01). After adjusting for alanine aminotransferase and alkaline phosphatase at 12 months, the use of predniso(lo)ne was found to be independently and negatively associated with recurrent disease. The rALD was found to be significantly associated with graft loss and patient survival in the multivariate Cox regression analysis with a time-dependent covariate. The 5- and 10-year probabilities of graft survival were 68% and 41% in patients with recurrent VS compared with 83% and 60% in patients without recurrent disease, respectively (p = 0.01). The overall survival was significantly reduced in patients with recurrent disease (p = 0.01), with event probability at 5 and 10 years of 75% and 49% vs. 84% and 60% in patients without recurrence, respectively. Conclusions: rALD after LT is frequent and is associated with elevation in liver enzymes within the first year after LT and rejection episodes. According to our data, VS recurrence appears to be associated with poorer graft and patient survival. Further studies are needed to explore strategies that can prevent VS recurrence or mitigate its potential impact. Impact and implications: This study investigated the recurrence of autoimmune liver diseases (rALD) in patients transplanted for variant syndromes (VSs) and its effect on graft and patient survival. The findings reveal a significant association between rALD and poorer graft and overall survival, highlighting the need for preventive strategies. This research is crucial for transplant physicians and healthcare providers, as it underscores the impact of early liver enzyme monitoring and tailored immunosuppressive therapy on long-term outcomes. These insights can inform more effective post-LT management protocols, potentially improving patient prognosis.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Autoimmunity; Liver transplantation; Recurrence